Don't forget the old - Abd Razak, Dzulkifli (2007)
"Enhancing competitiveness and sharing economic prosperity" this was the theme for the recent 2008 Budget dialogue chaired by the prime minister. The theme is consistent with the main thrust of the Ninth Malaysia Plan (20062010). There is a growing awareness worldwide that the primary goal of the government is no longer confined to the realm of creating wealth. Equally important, is the "creation of happiness". Consequently, the focus has shifted from tangible indicators such as gross domestic product to other measures such as general wellbeing (GWB).